Statistical Analysis of the Forensic Autopsies, Performed in the Department of Forensic Medicine of University Hospital Pleven for the Period 2009-2013 (A Preliminary Report) - Dancho Dekov; Ivan Ivanov; Sergey Kostadinov; Savelina Popovska; Petko Lisaev; Plamen Dorovski (Journal of Biomedical & Clinical Research, 2016)
The study is a statistical analysis of the dynamics and structure of forensic autopsies performed on dead bodies and body remains at University Hospital “Dr. Georgi Stranski” in Pleven. The study was based on forensic autopsy records database and forensic autopsy reports for the period 2009-2013. A total of 976 cases, including forensic autopsies, exhumations, examination of bone remains and inspection of dead bodies at the site of death (without following forensic autopsy), were analyzed. The studied data was coded and processed with Microsoft Excel software. A detailed data analysis of the number of autopsies, frequency of death by cause, distribution of death by gender, age, residence, place of death and its forensic category is presented. According to our results, the deaths due to diseases comprised 35% of all forensic autopsies. The most common cause of violent death was damage by mechanical factors (53%), followed by asphyxia (24.7%). The most common mechanical factor was vehicle crash trauma, followed by falling (22.5%). Accidents were the most common cause of death 62%, followed by suicides (31 %) and homicides 7%. Fifty-nine percent of the suicides were by hanging. The preliminary analyses of the studied data lead to several conclusions. The number of forensic autopsies was found to be progressively decreasing, but the road traffic death rate remained unchanged. Most of the forensic autopsies were performed in July. The highest death rates by age was observed in the age group between 51 and 60 years, with predominance of males over females (3.3 males: 1 females).